CT in the evaluation of the orbit and the bony interorbital distance. - Mafee, M F; Pruzansky, S; Corrales, M M; Phatak, M G; Valvassori, G E; Dobben, G D; Capek, V (American Journal of Neuroradiology, 1986)
The distance between the orbits and their individual dimensions are important in the diagnosis of craniofacial anomalies. Most observers rely on standard radiographs for measuring the bony interorbital distance. Tomography of the skull base and orbital computed tomography (CT) can also be used. This article describes the normal range of the bony interorbital distance and other useful orbital linear and angular measurements as determined from a series of CT scans of the orbits in 400 adults who had CT for other purposes. The normal interorbital distance measured at the posterior border of the frontal processes of the maxilla on nonrotated scans, in the plane of the optic nerve, ranges from 2.29 to 3.21 cm (average, 2.67 cm) in men and 2.29 to 3.20 cm (average, 2.56 cm) in women. The widest interorbital distance lies behind the posterior poles of the globes. This ranges from 3.16 to 4.10 cm (average, 3.37 cm) in men and 2.93 to 3.67 cm (average, 3.20 cm) in women.